Small but Significant: A Review of Research on the Potential of Bus Shelters as Resilient Infrastructure - Sarah Briant; Debra Cushing; Tracy Washington; Monique Swart (Applied Sciences, 2025)
Bus stops are an essential component of public transportation systems, significantly impacting human health, wellbeing, and overall user experience. As primary interaction points for passengers, they are integral to the urban landscape and, as such, their designs influence people’s experiences within the public realm. Despite their importance, the design of bus stops and bus shelters remains an under-researched area. This paper aims to review the existing peer-reviewed research on bus-stop design, identifying areas for future inquiry. Twenty-two peer-reviewed journal articles were selected and included in this study. The most common theme in the published research was the manner in which bus stops could address extreme weather and heat, along with other themes, including accessibility, sustainable energy, air pollution, and noise. Further empirical research is necessary to understand how bus-stop design affects the user experience, emphasizing qualitative methods to explore human experiences, perceptions, motivations, and challenges related to bus-stop usage and public transportation.